Comparison of 99mTc-Tetrofosmin and 99mTc-Sestamibi Uptake in Glioma Cell Lines: The Role of P-Glycoprotein Expression. (10th November 2014) - Alexiou, George A.; Xourgia, Xanthi; Vartholomatos, Evrysthenis; Tsiouris, Spyridon; Kalef-Ezra, John A.; Fotopoulos, Andreas D.; Kyritsis, Athanasios P.
Abstract : 99m Tc-Tetrofosmin ( 99m Tc-TF) and 99m Tc-Sestamibi ( 99m Tc-MIBI) are SPECT tracers that have been used for brain tumor imaging. Tumor's multidrug resistance phenotype, namely, P-glycoprotein (p-gp), and the multidrug resistance related proteins (MRPs) expression have been suggested to influence both tracers' uptake. In the present study we set out to compare 99m Tc-TF and 99m Tc-MIBI uptake in high-grade glioma cell lines and to investigate the influence of gliomas p-gp expression on both tracers' uptake. We used four glioma cell lines (U251MG, A172, U87MG, and T98G). The expression of p-gp protein was evaluated by flow cytometry. Twenty μ Ci (7.4·10 5  Bq) of 99m Tc-TF and 99m Tc-MIBI were used. The radioactivity in the cellular lysate was measured with a dose calibrator. P-gp was significantly expressed only in the U251MG cell line (P < 0.001 ). In all gliomas cell lines (U251MG, U87MG, A172, and T98G) the 99m Tc-TF uptake was significantly higher than 99m Tc-sestamibi. The U251MG cell line, in which significant p-gp expression was documented, exhibited the strongest uptake difference. 99m Tc-TF uptake was higher than 99m Tc-MIBI in all studied high-grade glioma cell lines. Thus, 99m Tc-TF may be superior to 99m Tc-MIBI for glioma imaging in vivo .